(untitled) (American Journal of Islam and Society, 2011)
Hooman Majd, a former writer for the Rolling Stone and movie producer, is uniquely qualified to write a book about Iran for an American audience. As he admits, “A friend once told me that that I was the only person he knew who was both 100 percent American and 100 percent Iranian. Oxymoronic as that sounds, I knew what he meant. I was raised and educated completely in the West, but am the grandson of a well-respected Alameh (learned) and Ayatollah; my first language is English, but I am also fluent in Farsi and am told that I speak it without an identifying accent. But more important, my Western outlook on life doesn’t interfere with my complete ease in the company of even the most radical of Iranian political or religious figures (and often theirs with me), and in my travels to Iran I have often thought there must be a toggle switch somewhere along the electrical system in my brain that is magically triggered to ʻEast’ when my plane crosses into Iranian airspace (8‒9).” Due to this toggle switch, Majd is able to highlight the very important role Persian culture plays in Iranian history and politics ‒ challenging the assumptions often made about Iranian clerics, politicians, and citizens ...